NLRP3 inflammasome activation by Paracoccidioides brasiliensis. - Aldo Henrique Tavares; Kelly Grace Magalhães; Raquel Das Neves Almeida; Rafael Correa; Pedro Henrique Burgel; Anamélia Lorenzetti Bocca (PLoS Neglected Tropical Diseases, 2013)
Paracoccidioides brasiliensis is the etiologic agent of paracoccidioidomycosis (PCM), the most prevalent systemic mycosis that is geographically confined to Latin America. The pro-inflammatory cytokine IL-1β that is mainly derived from the activation of the cytoplasmic multiprotein complex inflammasome is an essential host factor against opportunistic fungal infections; however, its role in infection with a primary fungal pathogen, such as P. brasiliensis, is not well understood. In this study, we found that murine bone marrow-derived dendritic cells responded to P. brasiliensis yeast cells infection by releasing IL-1β in a spleen tyrosine kinase (Syk), caspase-1 and NOD-like receptor (NLR) family member NLRP3 dependent manner. In addition, P. brasiliensis-induced NLRP3 inflammasome activation was dependent on potassium (K+) efflux, reactive oxygen species production, phagolysosomal acidification and cathepsin B release. Finally, using mice lacking the IL-1 receptor, we demonstrated that IL-1β signaling has an important role in killing P. brasiliensis by murine macrophages. Altogether, our results demonstrate that the NLRP3 inflammasome senses and responds to P. brasiliensis yeast cells infection and plays an important role in host defense against this fungus.